Boosting Ru atomic efficiency of LaFe 0.97 Ru 0.03 O 3 via knowledge-driven synthesis design - Wang, Yu; Paciok, Paul; Pielsticker, Lukas; Spriewald Luciano, Alexander; Glatthaar, Lorena; Xu, Aijie; He, Zimo; Ding, Min; Hetaba, Walid; Gallego, Jaime; Guo, Yanglong; Smarsly, Bernd M.; et al. (My University, 2025)
The exsolution of ruthenium from a 3 at% ruthenium-substituted LaFeO3 (LFR3) perovskite oxide is meticulously designed to produce a high-performance ruthenium-supported catalyst with high atomic efficiency. A high-temperature redox pretreatment at 800 °C enriches the Ru concentration in the near-surface region of LFR3, while a subsequent mild reduction step with H2 at 500 °C leads to the Ru exsolution from the Ru-enriched near-surface region (LFR3_Redox_500R), resulting in a high density of small particles that are not passivated by LaOx. The performance of this catalyst is evaluated through its application in two prototypical catalytic reactions: the combustion of propane (oxidation reaction) and the reduction of CO2 by hydrogenation (reduction reaction). For both reactions, the activity of the redox-pretreated sample LFR3_Redox_500R exhibits a significant increase compared to the activity of the untreated sample (LFR3_500R). In the catalytic hydrogenation of CO2, the high selectivity profile undergoes a transition from CO for LFR3_500R to methane for LFR3_Redox_500R.
Keywords: ddc:540